Role of Marginal Seas in Deep Ocean Regeneration of Dissolved Silica: A Case Study in the Marginal Seas of the Western Pacific - Yu, Xiaoqing; Zhuang, Yanpei; Cai, Xiaoxia; Qi, Di (Frontiers in Marine Science, 2022)
Deep ocean regeneration of dissolved silica (DSi) is an essential part of the ocean silica cycle and is driven by a complex series of biogeochemical processes. Here we compare the distributions of DSi and other environmental parameters in several western Pacific marginal seas to explore the role of marginal seas in deep ocean DSi regeneration. Results show that in oligotrophic marginal seas (such as the South China Sea), the DSi content in deep waters is similar to that of the adjacent Pacific waters. However, in productive marginal seas (such as the Bering Sea), the DSi content in deep waters is markedly higher than that in adjacent Pacific waters at the same depths. This is mainly due to deep ocean DSi regeneration in the marginal sea basin, which is fueled by the high biogenic particle flux from the productive surface waters. On a global scale, deep ocean DSi regeneration is accelerated in productive marginal seas, causing marginal seas such as the Bering Sea to have the highest DSi concentrations of all global waters.